THE SOUTHERN LITERATURE AND ITS BASIC FEATURES IN LITERATURE - Usmonova Dilyayra Rustamovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: During the Southern Renaissance, many significant changes and unprecedented works were created in American literature. Budavr literary samples are distinguished by several features. This article analyzes the emergence of the southern renaissance and some of its similarities and differences. Bright manifestations of the southern renaissance and their bright works are mentioned in the article.